The direct and indirect effect of neuroticism on work engagement of nurses during COVID-19: A temporal analysis - Vachhrajani, Mit; Mishra, Sushanta Kumar; Rai, Himanshu; Paliwal, Amit (Frontiers in Psychology, 2022)
Healthcare professionals such as nurses faced a tough time during the pandemic. Despite the personal and professional challenges, they contributed immensely during the pandemic. It is crucial to understand if individual personality influenced their work engagement and investigate situational factors that might have influenced nurses’ work engagement. Using the data from the nurses, we investigated the relationship between neuroticism and work engagement. We explored the positive and negative effects of pull (beneficiary contact) and push (fear of stigma) factors on the neuroticism-engagement relationship. Our results indicated that higher patient contact alleviated the adverse effect of neuroticism on work engagement. On the other hand, higher fear of stigma exacerbated the adverse effect of neuroticism on work engagement. Findings of the study highlighted the importance of societal factors and the policymakers in enhancing nurses’ work engagement.